OPTIMALISASI LOYALITAS, SEMANGAT, DAN DISIPLIN KERJA DALAM UPAYA MENINGKATKAN PRODUKTIVITAS KARYAWAN - Desi Rahmawati; Lona Chinsia Alfattama; Dian Respati Rindang (BEMJ : Business, Entrepreneurship, and Management Journal, 2022)
Abstract Employee productivity in managing an organization and institution is the driving force behind this study. This study is a descriptive qualitative study that uses data reductionanalysis techniques, data presentation, and data verification to show how the objectlimitations of loyalty, excitement, and work discipline were determined through the processof interviews, observation, and documentation. Using fingerprint attendance, implementingthe work culture of the Indonesian National Narcotics Agency, providing activities thatincrease cohesion, spiritual and mental development of employees, and enforcingdisciplinary measures are some of the steps taken to increase productivity of the NationalNarcotics Agency employees in Tulungagung Regency. Abstrak Penelitian ini dilatarbelakangi oleh produktivitas karyawan dalam mengelola suatu organisasi dan lembaga. Penelitian ini merupakan penelitian kualitatif yang bersifatdeskriptif, dimana data yang diperoleh melalui proses wawancara, observasi dandokumentasi yang mengenai batasan objek loyalitas, semangat, disiplin kerja dengan teknikanalisis reduksi data, penyajian data dan verifikasi data. Upaya yang dilakukan untukmeningkatkan produktivitas karyawan badan narkotika nasional kabupaten tulungagungadalah menggunakan absensi fingerprint, menerapkan budaya kerja BNN RI, menyajikankegiatan yang menambah kebersamaan, pembinaan rohani dan mental karyawan,memberikan sanksi terhadap karyawan yang melanggar aturan kedisiplinan.